Suggested methodology for longitudinal evaluation of nevi based on clinical images. Issue 1 (29th August 2021) - Reiter, Ofer; Musthaq, Shenara; Kurtansky, Nicholas R.; Barrios, Dulce M.; Halpern, Allan C.; Marchetti, Michael A.; Marghoob, Ashfaq A.; Nanda, Japbani K.; Stoll, Joseph; Rotemberg, Veronica
Abstract: Background: Melanoma screening includes the assessment of changes in melanocytic lesions using images. However, previous studies of normal nevus temporal changes showed variable results and the optimal method for evaluating these changes remains unclear. Our aim was to evaluate the reproducibility of (a) nevus count done at a single time point (method I) versus two time points (method II); and (b) manual and automated nevus diameter measurements. Materials and methods: In a first experiment, participants used either a single time point or a two time point annotation method to evaluate the total number and size of nevi on the back of an atypical mole syndrome patient. A Monte Carlo simulation was used to calculate the variance observed. In a second experiment, manual measurements of nevi on 2D images were compared to an automated measurement on 3D images. Percent difference in the paired manual and automated measurements was calculated. Results: Mean nevus count was 137 in method I and 115.5 in method II. The standard deviation was greater in method I (38.80) than in method II (4.65) ( p  = 0.0025). Manual diameter measurements had intraclass correlation coefficient of 0.88. The observed mean percent difference between manual and automated diameter measurements was 1.5%. Lightly pigmented and laterally located nevi had a higher percent difference. Conclusions: Comparison of nevi from two different time points is more consistent than nevus count performed separately at each time point. In addition, except for selected cases, automated measurements of nevus diameter on 3D images can be used as a time‐saving reproducible substitute for manual measurement on 2D images.